A Task and a Challenge for Several Generations of Researchers. Some Remarks on “The Legal and Research Challenges of Jewish Archaeology” by Dariusz Rozmus (“Prawne i badawcze wyzwania archeologii żydowskiej”. Oficyna Wydawnicza Humanitas. Sosnowiec 2022) - Aleksandra Namysło (Fasciculi Archaeologiae Historicae, 2023)
-